Kajian Normatif Tentang Tindak Pidana Pencemaran Nama Baik Di Dunia Maya - Saragih, Yasmirah Mandasari; Lubis, Muhammad Ridwan (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2019)
The purpose of this study was to determine how the validity or legal domicile Electronic Information and Electronic Documents as evidence in the criminal act of defamation in cyberspace as well as to determine the application of the law on criminal acts of defamation in cyberspace. By using the method of normative legal research, it can be concluded that: 1. In the event of the power and value of the evidence, the evidence provided for in Article 184 Criminal Procedure Code, which is the strength of evidence of electronic evidence is free (volledig bewijskracht) and is not binding or specify ( beslissende bewijskracht). Probative value of all evidence based on the judge's assessment. Setting electronic evidence in UU ITE regulated in Chapter III of Information, Document and Electronic Signature, as well as Article 44 of Law ITE. Article 5 (1) of the EIT set explicitly that information or electronic documents and / or printouts are valid evidence. Furthermore, Article 5 (2) states that "Electronic Information and / or Electronic Document and / or printout ... an extension of the valid evidence in accordance with the Law of Procedure applicable in Indonesia". This provision confirms that electronic evidence has been received in evidence in the Indonesian legal system. However, the emphasis of this section is setting elektronlk evidence in the Criminal Procedure Law in Indonesia. 2. For the application of the law, especially criminal sanctions against perpetrators of defamation in cyberspace (cyber), which is where the application of this law in the review of the Penal Code and the Law on ITE. Application of the law on criminal defamation baikinimenggunakan principle of Lex specialist derogat legi generali is where setting defamation in cyberspace regulated in Article 27 paragraph (3) and Article 45 of Law ITE is "Lex specialists" of Article 310 of the Criminal Code that is "Lex generali "which makes synergy relationship rules of law on defamation cases. Defamation cases conducted by Prita Mulyasari in cyberspace since the enactment of new EIT Law became part of the reference. Application of criminal sanctions alone unspecified and may be subject to penalties of imprisonment and fined.